2003
DOI: 10.4049/jimmunol.170.8.4011
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Characterization of T Cells Specific for BDC2.5 T Cell-Stimulating Peptides

Abstract: Nonobese diabetic (NOD) mice expressing the BDC2.5 TCR transgene are useful for studying type 1 diabetes. Several peptides have been identified that are highly active in stimulating BDC2.5 T cells. Herein, we describe the use of I-Ag7 tetramers containing two such peptides, p79 and p17, to detect and characterize peptide-specific T cells. The tetramers could stain CD4+ T cells in the islets and spleens of BDC2.5 transgenic mice. The percentage of CD4+, tetramer+ T cells increased in older mice, and it was gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(118 citation statements)
references
References 37 publications
5
113
0
Order By: Relevance
“…In these previous experiments, we have used the same cell culture protocol that we have used to expand and isolate N221 ϩ cells described in this report. Additional functional studies showed that, unlike N221 ϩ cells, these p79-specific T cells did not inhibit diabetes development (30). In addition, in another report we demonstrated that T cells cultured under the same culture conditions displayed the same cytokine secretion profiles as freshly isolated T cells before culture in vitro (20).…”
Section: Figurementioning
confidence: 64%
See 4 more Smart Citations
“…In these previous experiments, we have used the same cell culture protocol that we have used to expand and isolate N221 ϩ cells described in this report. Additional functional studies showed that, unlike N221 ϩ cells, these p79-specific T cells did not inhibit diabetes development (30). In addition, in another report we demonstrated that T cells cultured under the same culture conditions displayed the same cytokine secretion profiles as freshly isolated T cells before culture in vitro (20).…”
Section: Figurementioning
confidence: 64%
“…The tetAg7/p221 tetramer did not stain CD4 ϩ T cells specific for an irrelevant peptide, p79, isolated using tetAg7/p79 (tetAg7/p79 ϩ cells; Fig. 1B) (30). Additionally, these N221 ϩ cells were not stained positively by another control tetramer, tetAg7/p206, specific for a control p206 peptide.…”
Section: Purification and Characterization Of P221-specific T Cells Fmentioning
confidence: 96%
See 3 more Smart Citations